2013
DOI: 10.1155/2013/627412
|View full text |Cite
|
Sign up to set email alerts
|

Marked Ethnic, Nativity, and Socioeconomic Disparities in Disability and Health Insurance among US Children and Adults: The 2008–2010 American Community Survey

Abstract: We used the 2008–2010 American Community Survey Micro-data Sample (N = 9,093,077) to estimate disability and health insurance rates for children and adults in detailed racial/ethnic, immigrant, and socioeconomic groups in the USA. Prevalence and adjusted odds derived from logistic regression were used to examine social inequalities. Disability rates varied from 1.4% for Japanese children to 6.8% for Puerto Rican children. Prevalence of disability in adults ranged from 5.6% for Asian Indians to 22.0% among Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 19 publications
3
51
0
Order By: Relevance
“…Non-Hispanic African Americans had the highest prevalence of severe disability among all the racial groups included in the study, which is consistent with the available literature [1, 13, 14]. Previous studies have found that non-Hispanic African Americans are more likely to have disability due to low socioeconomic status, higher obesity, and higher rates of chronic condition compared to non-Hispanic Whites [1, 13, 14]. In our study, without adjustments for socioeconomic characteristics, non-Hispanic African Americans were 1.5 times as likely as non-Hispanic Whites to have severe disability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Non-Hispanic African Americans had the highest prevalence of severe disability among all the racial groups included in the study, which is consistent with the available literature [1, 13, 14]. Previous studies have found that non-Hispanic African Americans are more likely to have disability due to low socioeconomic status, higher obesity, and higher rates of chronic condition compared to non-Hispanic Whites [1, 13, 14]. In our study, without adjustments for socioeconomic characteristics, non-Hispanic African Americans were 1.5 times as likely as non-Hispanic Whites to have severe disability.…”
Section: Discussionsupporting
confidence: 90%
“…Worldwide, the number of individuals with disability is used as a marker for population health status because of high morbidity and mortality burden associated with disability [1]. According to the census, as of 2010, in the USA, across all ages, 18.7 % of the civilian, non-institutionalized population had some disability and 12.6 % had severe disability based on difficulty in performing functions and participation in activities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Routine screening for colorectal cancer has greatly increased since the 1980's, and has been largely credited for the reduction in CRC incidence. 4 However, Hispanics are less likely to be screened, [5][6][7] less likely to be insured, 8 and possibly less likely to utilize healthcare than other ethnic groups. 9,10 According to state cancer profiles (http://statecancerprofiles.cancer.gov/risk/index.php), the percentage of Hispanic males compliant with CRC screening recommendations in 2014 was 46.2% in the US and 44.9% in California.…”
Section: Introductionmentioning
confidence: 99%
“…51 Uninsurance rates among immigrant adults with disabilities are higher than among their US-born counterparts (e.g., 36% among Mexicans). 55 As such, poor uninsured immigrant persons with disabilities could be more susceptible to primary and preventive care access related barriers. 55 Social determinants, namely predisposing and enabling factors, play an important role in explaining differences in overall healthcare spending due to nativity among disabled working-age adults; the effects of these factors, however, might be limited depending on the type of healthcare service used.…”
Section: Discussionmentioning
confidence: 99%
“…55 As such, poor uninsured immigrant persons with disabilities could be more susceptible to primary and preventive care access related barriers. 55 Social determinants, namely predisposing and enabling factors, play an important role in explaining differences in overall healthcare spending due to nativity among disabled working-age adults; the effects of these factors, however, might be limited depending on the type of healthcare service used. This is in line with recent work showing that factors that influence access (e.g., insurance) among disabled individuals have mixed effects in explaining racial/ethnic and socioeconomic disparities in access to a variety of healthcare services.…”
Section: Discussionmentioning
confidence: 99%